61.8k views
4 votes
Need help answering this one

Need help answering this one-example-1
User Redronin
by
4.1k points

1 Answer

4 votes

Explanation:


((8.4.2)/(8.7) )^(2) * (\frac{ {8}^(0) }{{7}^( - 3) } )^(3 ) * {7}^( - 9) \\ \\ = ((8)/(7) )^(2) * (\frac{ 1}{{7}^( - 3) } )^(3 ) * {7}^( - 9)..... (\because a^0=1)\\ \\ = (64)/(49) * ({{7}^( 3) } )^(3 ) * {7}^( - 9) \\ \\ = (64)/(49) * {{7}^( 3 * 3) } * {7}^( - 9) \\ \\ = (64)/(49) * {{7}^( 9) } * {7}^( - 9) \\ \\ = (64)/(49) * {{7}^( 9 - 9) } \\ \\ =(64)/(49) * {{7}^( 0) } \\ \\ =(64)/(49) * 1 \\ \\ = (64)/(49)

Thus, first option is the correct answer.

User Zibi
by
4.7k points